The Effect of a Combination of Effleurage Massage and Lavender Aromatherapy on Back Pain in Third-Trimester Pregnant Women - Maulida Lathifah (Archives of The Medicine and Case Reports, 2023)
Every pregnant woman experiences different psychological and physiological changes in each quarter. Discomfort that occurs in the third trimester includes back pain. This study aimed to determine the effect of a combination of effleurage massage and lavender aromatherapy on back pain in third-trimester pregnant women. This study is a quantitative study with a one-group pretest-posttest design without control using a purposive random sampling technique. The research was conducted in February-April 2023 with 30 pregnant women as respondents. Data collection techniques using observation sheets. Using univariate and bivariate analysis methods. The results of the study showed that there were differences in the intensity of back pain before and after the intervention, p<0.05. The combination of effleurage massage and lavender aromatherapy can significantly reduce back pain in third-trimester pregnant women.